Archive of Our Own as an Informal Digital Learning Environment for English Vocabulary Development - Suni, Fauziyyah Mufida; Margana, Margana (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
Vocabulary demands in higher education often exceed the English repertoire of Indonesian university students. Therefore, they need supplementary resources. While Informal Digital Learning of English (IDLE) is gaining traction, research on fanfiction-based practices within higher education contexts remains notably limited. Addressing this gap, this study examined how the fanfiction platform Archive of Our Own (AO3) functions as an IDLE environment for lexical development. Using an explanatory sequential mixed-methods design, data were collected from 30 university students via comprehensive questionnaires. Descriptive results indicated students primarily engaged with AO3 for enjoyment, perceiving it as highly beneficial for vocabulary growth and exposure to authentic English. Thematic analysis revealed that this lexical expansion occurred incidentally during reading, supported by autonomous strategies such as contextual inference, dictionary use, note-taking, and rereading. However, participants were tentative about AO3’s impact on understanding university-level texts, suggesting its value lies more in general vocabulary enhancement than in targeted academic instruction. This study contributes to IDLE research by illustrating how fanfiction integrates intrinsic motivation, incidental word acquisition, and learner autonomy. Pedagogically, AO3 can be considered a supplementary learning resource.